2013
DOI: 10.1371/journal.pone.0059558
|View full text |Cite
|
Sign up to set email alerts
|

Glioma Initiating Cells Form a Differentiation Niche Via the Induction of Extracellular Matrices and Integrin αV

Abstract: Glioma initiating cells (GICs) are considered responsible for the therapeutic resistance and recurrence of malignant glioma. To clarify the molecular mechanism of GIC maintenance/differentiation, we established GIC clones having the potential to differentiate into malignant gliomas, and subjected to DNA microarray/iTRAQ based integrated proteomics. 21,857 mRNAs and 8,471 proteins were identified and integrated into a gene/protein expression analysis chart. Gene Ontology analysis revealed that the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…Our phosphoproteomic result indicated that the phosphorylation levels at Ser 21 and Tyr 420 were elevated in serum-free cultured GB2 cells, which reflected the previous evidence that the high phosphorylation level of Tyr 420 on Fyn was observed in clinical samples from glioblastoma patients (44). In serum cultured GB2 cells, the functional sites for the kinase activity of MAPK1 (Thr 185 / Tyr 187 ) and MAPK3 (Tyr 204 ) were also highly phosphorylated in agreement with the previous study regarding glioblastoma stem cells (14).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our phosphoproteomic result indicated that the phosphorylation levels at Ser 21 and Tyr 420 were elevated in serum-free cultured GB2 cells, which reflected the previous evidence that the high phosphorylation level of Tyr 420 on Fyn was observed in clinical samples from glioblastoma patients (44). In serum cultured GB2 cells, the functional sites for the kinase activity of MAPK1 (Thr 185 / Tyr 187 ) and MAPK3 (Tyr 204 ) were also highly phosphorylated in agreement with the previous study regarding glioblastoma stem cells (14).…”
Section: Discussionsupporting
confidence: 90%
“…Fyn-mediated phosphorylation of this molecule are known to contribute to promote self-renewal and tumor formation of glioblastoma stem cells (32). The phosphorylated Thr 185 /Tyr 187 residues of MAPK1 and Tyr 204 of MAPK3 were also reported to be up-regulated in glioblastoma stem cells after serummediated loss of stem-like characteristics in the previous study (14).…”
Section: Effect Of Serum-containing Culture On Glioblastoma Stemmentioning
confidence: 79%
See 2 more Smart Citations
“…GIC stays in a niche reported to be composed of stem cells, supportive cells, serum growth factors, immunological cells and eCM [76,77] . The αV integrin, one of the key factors of eCM, seems to have a pivotal role in the increased pathological outcome of the GIC.…”
mentioning
confidence: 99%